Smith, Ed., The Holocaust And Other Genocides - History, Representation, Ethics - Cole, Jeffrey (Teaching History: A Journal of Methods, 2006)
There is no shortage of Holocaust-related literature on the academic textbook market, but when it comes to works that offer a comparative approach to genocide, instructors find little of value. The Holocaust and Other Genocides is a notable exception. Helmut Walser Smith's concise volume is a treasure. Filled with primary source material related to the Holocaust, Armenian genocide, events in Bosnia and Kosovo, and Rwanda, the book's format provides students with the tools they need to think deeply about some of the twentieth century's worst crimes. The first half of the book is dedicated to the Holocaust. Section I, entitled "History of the Holocaust," opens with images of Jews in the medieval period and an anti-Semitic statement from Martin Luther. Subsequent documents include photographs from 1930s Germany; excerpts from the Nuremberg Laws; a 1943 German railway schedule that shows how many passengers were transported and to where; and an excerpt from a Warsaw Ghetto diary.